Appendix 4.21: Marcos Diary Entries, 8 October 1970 and 11 June 1979 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
These entries show what else one can find in Marcos’s diaries—musings, his views on certain crucial events, and his take on his powers under martial law. The 1970 entry mentions several of Marcos’s desired legislative legacies and his planned programs for the poor. About half of the entry concerns how history will judge him. Here, he declares that to combat distortion by contemporary writers of history, he will write about the first four years of his administration himself. That volume did not materialize; the first book authored by Marcos was the lengthy political philosophy essay, Today’s Revolution: Democracy (1971). In the 1979 entry, Marcos clarifies that the Ministry of National Defense (then headed by Juan Ponce Enrile) “has no command function,” i.e., is only recommendatory. Marching orders of the Armed Forces can only be promulgated by Marcos as Commander-in-Chief. However, it is also implied that Enrile had previously exercised command functions (e.g., the transfer of the 60th Philippine Constabulary Strike Force Battalion; see appendix 2.5, 389) though Marcos, to “maintain a semblance of unity in the administration,” maintained that such were done upon his orders.